Constraints To The National Narcotics Agency's Synergity With The Center For Financial Transaction Reporting And Analysis In Preventing And Eradicing The Crime Of Money Laundering In The Narcotics Business - Novy Setyorantiningsih; Bayu Mahendra; Aryo Harry W; Mohamad Adrian Jufril; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The circulation of narcotics by organized crime continues to increase and even seeks to disguise or eliminate the proceeds of narcotics crime by laundering money through financial institutions or by investing in economic activities. The problem in this study is regarding efforts to overcome the synergy constraints of BNN (National Narcotics Agency) and PPATK (Financial Transaction Reporting and Analysis Center) in preventing and eradicating money laundering crimes from the narcotics business. This study uses normative legal research (library) to draw conclusions about efforts that can be made in synergy between BNN and PPATK in preventing and eradicating criminal acts of laundering from the narcotics business, namely collaboration with related institutions and agencies, increasing the exchange or request for information and statistical data. speedy handling of narcotics crime cases as well as improving PPATK's performance and updating the agreements set forth in the MoU